LITERATURE AS REFERENCE FOR A PHILOSOPHY OF MAN-AND-TIME, AS GIVEN IN LATIN-AMERICA - Vázquez, W. (Revista Letras, 1969)
LITERATURE AS REFERENCE FOR A PHILOSOPHY OF MAN-AND-TIME, AS GIVEN IN LATIN-AMERICA